Integrating the Cross-Border Industrial Chain: An Exploring of Key Configuration of Agricultural Investment in Lancang-Mekong River Region - Feng L; Yang W; Jin Y; Zhang Y; Li B (MDPI (Basel, Switzerland), 2025)
The demand for agriculture finance and investment for sustainable agriculture development has long been a concern for many years. However, the insufficient integration of the agricultural technology innovation chain and technology transfer impedes the enhancement of collaborative innovation capability in evolving total factor productivity. This paper utilizes Chinese agricultural companies’ investment in the Lancang-Mekong River region as an example to scrutinize key configuration factors fostering the integration of technical collaboration within agricultural industry chains. The results indicated that Chinese agricultural companies can be classified into two categories based on their approach to technical collaboration. The first category is strength-oriented, and companies in this category have the capability to transform technological investments, yielding relatively high returns. They also have optimistic expectations regarding favorable policies in the host country. This category accounts for about one-third of the companies studied. The second category is potential-oriented, in which firms possess the potential for technological investment transformation, with lower investment returns. They require effective contextual management and tax incentives from the host country to thrive. The impact of foreign direct investment decision-making diminishes, introducing new imperatives for the current host country’s market environment and the management of FDI enterprises in the host country. This study makes contributions to advance the exploration of technology’s impact on agricultural companies’ cross-border investment, stipulating new requirements for the transformative development of regional foreign direct investment, particularly for private enterprises.
Keywords: agricultural industrial chain; foreign direct investment; technical integration; fsQCA